SEJARAH PERKEMBANGAN MATEMATIKA YUNANI KUNO DAN TOKOH-TOKOHNYA - Khurotun Lutfi Khafifah; Lutfiana Dwi Safitri; Nova Yulianasari (UPT Penerbitan Universitas Jember, 2022)
The purpose of this study is to encourage readers to understand the history of Ancient Greek mathematics and the personalities that shaped it. This research focuses on library research, gathering information from books, scientific publications, and the internet. In contrast to Egypt and Babylonia, the research findings reveal that mathematics emerged in Ancient Greece without written literature. Ancient Greek mathematicians used deductive reasoning. Thales, Pythagoras, Aristotle, and Plato were important figures in the development of ancient Greek mathematics. Keywords: Matematika,Yunani,Geometri